2013
DOI: 10.1155/2013/108912
|View full text |Cite
|
Sign up to set email alerts
|

The Study of a Dual-Disk Type Piezoelectric Actuator

Abstract: This study presents an innovative piezoelectric actuator, capable of long travel distance and fast speed. Main components of the actuator include a rod and two piezoelectric buzzers of disk geometry. Being subject to the piezoelectric force and Coulomb friction, the piezoelectric actuator can move rapidly. Equations of motion are derived based on piezoelectric properties and Newton's law. Static and kinetic friction effects are incorporated. Stress and strain calculations and piezoelectric equations are includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…linear sawtooth without plateau [78,249] linear sawtooth with two plateaus [24,26,117,250] square, pulse [78,138,200,[251][252][253][254][255] two superposed sines [68,77,85,86,94,171] (b) Matsuda and Kaneko [45] present a motor operating with single cosine waves. This demonstrates that an inertia motor in single-step operation does not necessarily require an asymmetric driving signal, but this signal remains unique in literature.…”
Section: Voltage Signals For Low-frequency Operationmentioning
confidence: 99%
“…linear sawtooth without plateau [78,249] linear sawtooth with two plateaus [24,26,117,250] square, pulse [78,138,200,[251][252][253][254][255] two superposed sines [68,77,85,86,94,171] (b) Matsuda and Kaneko [45] present a motor operating with single cosine waves. This demonstrates that an inertia motor in single-step operation does not necessarily require an asymmetric driving signal, but this signal remains unique in literature.…”
Section: Voltage Signals For Low-frequency Operationmentioning
confidence: 99%
“…Chen et al reported on an inertial piezoelectric linear actuator based on dual discs [4]. Operation of the actuator based on inertial stick -slip principle which is obtained via simultaneously excited piezoelectric bimorph discs by a single rectangular excitation signal whose frequency was equal or close to the first bending mode of discs.…”
Section: Introductionmentioning
confidence: 99%